2019
DOI: 10.1155/2019/4052168
|View full text |Cite
|
Sign up to set email alerts
|

Association of Ulcerative Colitis with FOXP3 Gene Polymorphisms and Its Colonic Expression in Chinese Patients

Abstract: Abnormalities of forkhead box P3 (FOXP3) are implicated in various autoimmune diseases. This study is aimed at investigating the association of ulcerative colitis (UC) with FOXP3 polymorphisms and its colonic expression in Chinese patients. Polymorphisms of rs3761548, rs2232365, rs2294021, and rs3761547 were examined in 472 UC patients and 525 healthy controls using the SNaPshot method. The colonic expression of FOXP3 mRNA and protein was assayed in inflammatory mucosa of 34 UC patients and normal mucosa of 36… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
20
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(21 citation statements)
references
References 37 publications
0
20
1
Order By: Relevance
“…Ulcerative colitis affects the large bowel and the associated clinical manifestations include chronic hemorrhagic diarrhea, abdominal cramps and pain, gut perforation, and complete bowel obstruction, which significantly affect the quality of life of the ailing person. The precise etiology of the disease is not well recognized; however, host genetic factors, immune disequilibrium, environmental factors, and host-microbial composition are believed to be responsible for the development and progression of the disease (Loftus, 2004, Hatoum and Binion, 2005, Xia et al, 2019, Kengo et al, 2019). Current medical interventions for managing IBD are not satisfactory and does not lead to complete remission of symptoms.…”
Section: Introductionmentioning
confidence: 99%
“…Ulcerative colitis affects the large bowel and the associated clinical manifestations include chronic hemorrhagic diarrhea, abdominal cramps and pain, gut perforation, and complete bowel obstruction, which significantly affect the quality of life of the ailing person. The precise etiology of the disease is not well recognized; however, host genetic factors, immune disequilibrium, environmental factors, and host-microbial composition are believed to be responsible for the development and progression of the disease (Loftus, 2004, Hatoum and Binion, 2005, Xia et al, 2019, Kengo et al, 2019). Current medical interventions for managing IBD are not satisfactory and does not lead to complete remission of symptoms.…”
Section: Introductionmentioning
confidence: 99%
“…131 Recently, the risk of ulcerative colitis in a Chinese population was proposed to be associated with single-nucleotide polymorphisms in the human FOXP3 locus, which could be associated with diminished numbers or function. 132 Studies have found lower levels of Treg cells in the lamina propria in IBD and increased apoptosis of these cells. 133,134 Infliximab treatment of patients with active IBD diminished Treg apoptosis.…”
Section: Tnf Inhibitor Family: Modulation Of the Immune System To Control Inflammation And Unintentional Regulation Of The Patient's Tregmentioning
confidence: 99%
“…It has been reported that FOXP3 gene expression is excessively increased in HBV patients with cirrhosis who have a very advanced immune-active HBV phase 20 . In addition to this, some studies reported that the FOXP3 expression was up-regulated in the inflamed colonic mucosa to prevent intestinal inflammation 14,21 . Especially, the rs2232365 and rs3761548 polymorphisms influence FOXP3 expression because of located within the DNAbinding sites of GATA-3 and Sp-1 transcription factors in the promoter region of the FOXP3 gene 13,22 .…”
Section: Discussionmentioning
confidence: 95%
“…Thereby, Treg cells prevent an aggressive T cell response to antigens and provide immune homeostasis. FOXP3 expression' down-regulation or dysfunction is related to immunological and inflammatory diseases such as multiple sclerosis 11 , rheumatoid arthritis 12 , vitiligo 13 , ulcerative colitis 14 , and chronic HBV infection 15 .…”
Section: Introductionmentioning
confidence: 99%